2018
DOI: 10.1038/s41419-018-0323-5
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cell-derived extracellular vesicles promote lung adenocarcinoma growth by transferring miR-410

Abstract: Although accumulating evidence has linked mesenchymal stem cells (MSCs) with tumor growth, the underlying mechanisms are poorly understood. Here, we demonstrated for the first time that human umbilical cord MSCs (hUCMSCs) dramatically increased the growth of lung adenocarcinoma (LUAD) cancer cells in a xenograft tumor model. Then, we observed that hUCMSC-derived extracellular vesicles (hUCMSC-EVs) contribute to the hUCMSC-promoted LUAD cell growth through a direct effect on LUAD cells. Furthermore, we showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 54 publications
5
111
0
Order By: Relevance
“…We successfully extracted hUCMSC‐EVs, which presented a cup‐shaped membrane structure when viewed through TEM. The sizes and shapes of the hUCMSC‐EVs that we obtained in the present study are consistent those of hUCMSC‐EVs that we collected in a previous work …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We successfully extracted hUCMSC‐EVs, which presented a cup‐shaped membrane structure when viewed through TEM. The sizes and shapes of the hUCMSC‐EVs that we obtained in the present study are consistent those of hUCMSC‐EVs that we collected in a previous work …”
Section: Discussionsupporting
confidence: 91%
“…These tests revealed that hUCMSCs have osteogenic and adipogenic differentiation potential. 17 Phycoerythrin (PE)-conjugated CD14, CD19, CD34, CD45, CD73…”
Section: Isolation and Characterization Of Hucmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…These MSC properties of cancer support are originally licensed by tumorinfiltrating macrophages which establish a pro-inflammatory chemotactants-studded milieu (Coffelt et al, 2009;Rigo et al, 2010). This milieu evokes MSCs to (i) differentiate into highly proliferative myofibroblasts (Von Ahrens et al, 2017) and vascular cells , (ii) produce tumor-nurturing pro-angiogenic cytokines, miRNA, and exosomes (Roccaro et al, 2013;Zhang et al, 2013;Dong et al, 2018), (iii) secrete extracellular matrix-forming lysosomal oxidase (El-Haibi et al, 2012), (iv) provide a niche for malignant cells to thrive (Lin et al, 2019), and (v) adopt the immunomodulatory MSC2 phenotype (see section "Immunological Properties: A Paradigm") (Patel et al, 2010). As previously mentioned, MSC2 further polarizes macrophages into the M2 phenotype which is pro-tumorigenic (Rivera-Cruz et al, 2017).…”
Section: Cancer Support or Suppression?mentioning
confidence: 99%
“…Interestingly, the levels of miR‐410 were notably enhanced in lung adenocarcinoma cells after incubation with hUCMSC‐EVs. Phosphatase and tensin homolog (PTEN) was found to be directly regulated by miR‐410 as evidenced by reduced PTEN levels in the tumors of hUCMSC‐EV‐pre‐treated mice …”
Section: Role Of Mir‐410 As An Oncogene: a Maestro With A Rapidly Incmentioning
confidence: 99%